Classification of seafloor characteristics in a glacial marine environment: Potter Cove, King George Island, Antarctica - Wölfl, Anne-Cathrin; Wittenberg, Nina; Hass, Christian (2012)
The modern sedimentation pattern and the occurrence of geomorphological features in a glacial marine environment have been studied based on grab samples for granulometry analysis and sidescan sonar records for objectoriented classification. Furthermore, there was an attempt to generate a spatial habitat map using an acoustic ground discrimination system (AGDS). Hydroacoustics are often used in marine sciences, since they have the advantage to rapidly map large areas in high resolution compared to more traditional methods. In addition, underwater videos for visual characterization were used for ground-truthing the hydroacoustic data set. The survey was carried out with zodiacs in the austral summer season of 2010/2011 and 2011/2012 on the Argentine Carlini base (formerly known as Jubany base). The study area in Potter Cove isa tributary inlet that opens up to Maxwell Bay, one of the two large fjordic systems on King George Island. This region experiences regional winter warming since more than 50 years, which resulted in signifi cant glacial retreat changing the terrestrial and marine environment ever since. The sediment distribution in the cove seems mainly be influenced by the sediment-laden meltwaters, rather than by currents transporting allochthonous material into the system. The sidescan sonar records reveal geomorphological features such as plough marks, sink holes and ridges that point to significant glacial influence in the past and at present times. The data set obtained by the AGDS shows acoustically distinctive regions in the cove. It is now subject of ongoing investigations how many different habitats can be determined by this data.